So hard to care…critical care nursing in Hellas - Papathanassoglou, Elizabeth (My University, 2006)
How will more knowledge help? I have my patients, I have my orders, I know my way. When the shift is over I go home and that’s the end of it. We need to face it, the decisions are not ours to make [means clinical decision making], they [physicians] make the decisions, they do not listen to what we have to say, and we might have something to suggest. I used to read a lot, I attend seminars and conferences, there are things we can do. NURSING [interviewee’s emphasis] things that will help them [means the patients]. But even nurses do not care, we are exhausted not able to endure any more you know we work for weeks without a day off? . Yet we are invisible, they do not respect us. It is US, WE are the problem. It is like nursing is not a profession. we are scared to argue. Do not get me wrong, I do believe our contribution, what we have to offer to patients, is TREMENDOUS. BUT only because we CARE, WE CARE for them [means the patients]. It is so hard to care
Keywords: Critical care nursing; Greece; Burnout (Psychology); Nurses--Attitudes; Intensive care nursing